Bacteria commonly associated with central nervous system catheter infections elicit distinct CSF proteome signatures - Beaver, Matthew; Noe, Dragana; Thapa, Ishwor; Ali, Hesham; Snowden, Jessica; Kielian, Tammy; Skar, Gwenn L. (Frontiers in Neurology, 2023)
Background Cerebrospinal fluid (CSF) shunt infection is a common and devastating complication of the treatment of hydrocephalus. Timely and accurate diagnosis is essential as these infections can lead to long-term neurologic consequences including seizures, decreased intelligence quotient (IQ) and impaired school performance in children. Currently the diagnosis of shunt infection relies on bacterial culture; however, culture is not always accurate since these infections are frequently caused by bacteria capable of forming biofilms, such as Staphylococcus epidermidis, Cutibacterium acnes, and Pseudomonas aeruginosa resulting in few planktonic bacteria detectable in the CSF. Therefore, there is a critical need to identify a new rapid, and accurate method for diagnosis of CSF shunt infection with broad bacterial species coverage to improve the long-term outcomes of children suffering from these infections. Methods To investigate potential biomarkers that would discriminate S. epidermidis, C. acnes and P. aeruginosa central nervous system (CNS) catheter infection we leveraged our previously published rat model of CNS catheter infection to perform serial CSF sampling to characterize the CSF proteome during these infections compared to sterile catheter placement. Results P. aeruginosa infection demonstrated a far greater number of differentially expressed proteins when compared to S. epidermidis and C. acnes infection and sterile catheters, and these changes persisted throughout the 56-day time course. S. epidermidis demonstrated an intermediate number of differentially expressed proteins, primarily at early time points that dissipated over the course of infection. C. acnes induced the least amount of change in the CSF proteome when compared to the other pathogens. Conclusions Despite the differences in the CSF proteome with each organism compared to sterile injury, several proteins were common across all bacterial species, especially at day 5 post-infection, which are candidate diagnostic biomarkers.